Implementation of Parenting Education in Early Childhood Education Institutions - Baroroh, Siti Arini; Budiartati, Emmy; Fakhruddin, Fakhruddin (Journal of Nonformal Education, 2020)
One of the successes of early childhood education is the involvement of parents in their children’s education. Parenting education is one aspect of achieving these educational goals. The purpose of this study is to describe the implementation of parenting education in Pendidikan Anak Usia Dini Institutions as well as supporting and inhibiting factors in the application of parenting education. This research uses a qualitative research approach. Data collection methods used are interviews, observation, and documentation. Research subjects were conducted on 6 parents of students and 3 informants, namely educators and educational staff. The validity of the data uses triangulation techniques and uses qualitative data analysis. The results showed that parenting education has programmed planning to start from the implementation objectives, implementing organizations to competent resource persons, but has not paid attention to the reference in its implementation and has not identified the needs of parents in planning activities. Parenting education is carried out in various forms of routine and incidental activities. Supporting factors are the commitment of educators and parents in running the program, the availability of adequate facilities and infrastructure. Inhibiting factors are low parenting awareness and busy working parents resulting in low involvement in activities. Parenting education is very important for a better child’s life, for that there needs to be good management in every early childhood education.